Contemporary consumer perspectives on prostate cancer survivorship: Fifty voices. Issue 3 (15th January 2020) - Dunn, Jeff; Ralph, Nicholas; Green, Anna; Frydenberg, Mark; Chambers, Suzanne K.
Abstract: Objective: To describe contemporary consumer experiences and priorities of prostate cancer survivorship to inform the development of survivorship guidelines. Method: In a cross‐sectional qualitative design, semi‐structured interviews were undertaken with fifty prostate cancer support group leaders (50% response) across urban and rural/regional Australia. An interpretative phenomenological approach was used to identify participants' experiences and priorities of survivorship. Results: Three themes were identified for informing the development of prostate cancer survivorship guidelines: (a) the Experience of Diagnosis and Treatment, (b) Priorities for Survivorship and (c) Mechanisms for Support. Four priorities for prostate cancer survivorship were: delivering person and men‐centred care; improving communication; improving care coordination; and facilitating access to care. Mechanisms for support were as follows: advocacy; peer support; prostate cancer specialist nurses; and communication training for health professionals. Conclusions: The lack of progress in changing prostate cancer survivorship outcomes for men will become increasingly problematic as this patient population group grows. Co‐production provides a way forward to ensure relevance and accessibility for future survivorship initiatives.